Therapeutic Communication in Mental Health Telemedicine Services Through the Halodoc Application - Lisnarini, Naurah; Ratna Suminar, Jenny; Setianti, Yanti (Mediator: Jurnal Komunikasi, 2024)
This qualitative study explores the communication dynamics between psychologists and clients within the framework of utilising mental health services provided by Halodoc. Telemedicine has emerged as a popular alternative for individuals seeking mental health support in the digital age. Using a case study methodology, in-depth interviews were conducted with psychologists and clients who availed themselves of Halodoc’s mental health features. The findings reveal both advantages and challenges associated with communication via Halodoc. Advantages include enhanced accessibility, convenience, and privacy for clients, while challenges encompass the absence of non-verbal cues, difficulties in building rapport, and occasional technical constraints affecting session quality. This research offers valuable insights into the communication dynamics of digital mental health services, laying the groundwork for enhancing service efficacy and user experience. In conclusion, the study emphasises the need to address challenges within telemedicine platforms and continuously improve them to optimise mental health service delivery in the digital realm. Ultimately, the study contributes to advancing our understanding of communication in digital mental health services and underscores the importance of ongoing refinement in telemedicine platforms to meet the evolving needs of clients and psychologists alike.